Postural changes versus balance control and falls in community-living older adults: a systematic review - Viviane Lemos Silva Fernandes; Darlan Martins Ribeiro; Luciana Caetano Fernandes; Ruth Losada de Menezes (Editora Champagnat, 2018)
Abstract Introduction: Since falls are considered to be a public health problem, it is important to identify whether postural changes over time contribute to the risk of falls in older adults. Objective: To investigate whether postural changes increase fall risk and/or postural imbalance in healthy, community-dwelling older adults. Methods: In April 2016, two reviewers independently searched the PubMed, Web of Science, SPORTDiscus, and CINAHL databases for studies in English published in the previous 10 years, using the following combined keywords: "posture" or ("kyphosis","lumbar lordosis","flexed posture","spinal curvature","spinal sagittal contour") AND "elderly" AND "fall". Study quality was assessed according to the STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) guidelines for observational studies. Results: The search retrieved 1,734 articles. Only observational studies that assessed posture, balance, and/or falls in older adults were considered eligible for review. The final sample included 17 articles: reliability and reproducibility of the instruments were not reported in five studies, while two studies offered a questionable description of the instruments used. Fourteen articles analyzed postural changes at the trunk level and three articles assessed them at the ankles and feet. Most studies found a positive association between postural changes and an increased risk for loss of balance and falls. Conclusion: Thoracic hyperkyphosis, loss of lumbar lordosis, and decreased plantar arch seem to contribute to greater postural instability, and thus to a higher risk of falls in community-living older adults.